Using waste CO2 from corn ethanol biorefineries for additional ethanol production: life‐cycle analysis. (17th December 2020) - Lee, Uisung; R Hawkins, Troy; Yoo, Eunji; Wang, Michael; Huang, Zhe; Tao, Ling
Abstract: Corn ethanol plants generate high‐purity carbon dioxide (CO2 ) while producing ethanol. If that CO2 could be converted into ethanol by carbon capture and utilization technologies it would be possible to increase ethanol production more than 37% without additional corn grain inputs. Gas fermentation processes use microbes to convert carbon‐containing gases into ethanol and so have the potential to be used with the CO2 from biorefineries for this purpose. However, as CO2 utilization technologies for converting thermodynamically stable CO2 are typically energy intensive, it is necessary to evaluate the related life‐cycle greenhouse gas (GHG) emissions (carbon intensities or CIs) to see whether there are actual emission reduction benefits. In this study, we evaluate the CIs of ethanol produced from high‐purity CO2 in corn ethanol plants by gas fermentation plus electrochemical reduction. Our analysis shows that the sources of electricity and hydrogen are key drivers of CO2 ‐based ethanol's GHG emissions. With wind electricity, the design cases show the potential of near‐zero CI ethanol (1.1 g CO2 e/MJ), but that can increase to up to 331–531 g CO2 e/MJ when today's U.S. Midwest electricity mix is used. To avoid the renewable electricity intermittency issue, we considered a power purchase agreement option using wind electricity 40% of the time and using the regional mix for the rest, which provides a 42% GHG emission reduction from the CI of gasoline. © 2020 The Authors and UChicago Argonne, LLC, Operator of Argonne National Laboratory. Biofuels, Bioproducts and Biorefining published by Society of Chemical Industry and John Wiley & Sons, Ltd.